Production and Characterization od Xylanase from Actinomyces ATG 70 Using CornCob Xylan Substrate - Farrennina, Tasya Preira; Putri, Amelia Fahreza; Arimurti, Sattya; Winarsa, Rudju; Utarti, Esti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Xilan is a polysaccharide that can be used as a substrate for producing xylanase. Xylan can be obtained from processing xylan-rich agricultural waste such as corn cobs, which contain 12.4% xylan. Xilan can be hydrolyzed into xylose and xylooligosaccharide (XOS) using the enzyme Xilanase. Actinomycetes have dominant xylanolytic species, Actinomyces ATG 70 has semi-qualitative xylanolytic ability with an enzyme activity index of 3.21±0.55 in xylan media. This study was conducted by extracting xylan from corn cobs, rejuvenating Actinomyces ATG 70, preparing the inoculum, creating a standard curve, producing xylanase with pH optimization of the medium, testing xylanase activity, characterizing the pH and temperature of crude xylanase, and identifying the morphology and biochemical characteristics of Actinomyces ATG 70. Optimization of the pH of the xylanase production medium was achieved at pH 8, with xylanase activity of 10.07±0.13 U/mL. The crude xylanase was characterized for pH and temperature effects, and the optimal pH for crude xylanase was found to be pH 6 with xylanase activity of 7.64±0.66 U/mL, and the optimal temperature was 50°C with xylanase activity of 11.17±0.33 U/mL. The identification results showed that Actinomyces ATG 70 belongs to Gram-positive bacteria, with a positive catalase test, white colonies, cream-colored aerial mycelium, and cream-colored pigmentation. The spore structure consists of long chains of conidia, streptococcus-shaped cells, and can form aerial mycelium, thus the isolate belongs to the genus Streptomyces.